2019
DOI: 10.1016/j.tranon.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Anti-ADAM17 Antibody A9(B8) Enhances EGFR-TKI–Mediated Anticancer Activity in NSCLC

Abstract: Epidermal growth factor receptor (EGFR) mutations were found in 30%-40% of non–small cell lung cancer (NSCLC) patients, who often responded well to EGFR tyrosine kinase inhibitors (EGFR-TKIs) as exemplified by erlotinib and gefitinib in the past decades. However, EGFR mutation-led drug resistance usually occurred upon prolonged treatment with EGFR-TKI. Herein, we study the anticancer effects of EGFR-TKI in combination with a newly developed antibody, A9(B8), to target a disintegrin and metalloprotease (ADAM) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is estimated that approximately 25% of cancer cases are related to infectious diseases and chronic inflammation (40). The reduction of inflammatory molecule production has been shown to enhance the sensitivity of NSCLC with EGFR mutation to EGFR-TKIs (41). In support of the hypothesis that inflammation is associated with cancer development and progression and also influence the response to treatment, we found that 3 SNPs (rs10519613, rs4819554, and rs4149570) and 5 SNPs (rs10519613, rs4819554, rs2070600, rs755622, and rs4149570) were associated with worse PFS and OS of advanced NSCLC patients treated with EGFR-TKIs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 25% of cancer cases are related to infectious diseases and chronic inflammation (40). The reduction of inflammatory molecule production has been shown to enhance the sensitivity of NSCLC with EGFR mutation to EGFR-TKIs (41). In support of the hypothesis that inflammation is associated with cancer development and progression and also influence the response to treatment, we found that 3 SNPs (rs10519613, rs4819554, and rs4149570) and 5 SNPs (rs10519613, rs4819554, rs2070600, rs755622, and rs4149570) were associated with worse PFS and OS of advanced NSCLC patients treated with EGFR-TKIs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In lung adenocarcinoma tissues, the number of phospho-ADAM17-positive cells was significantly increased in KRAS-mutated tumors than in the tumors with wild-type KRAS [89]. Additionally, ADAM17 is highly expressed in EGFR-mutated NSCLC cells, where an anti-ADAM17 antibody enhances EGFR-TKI-mediated growth inhibition, which is accompanied with reduced ERK phosphorylation [90]. Therefore, it is possible that such oncogenic drivers induce the EREG-mediated oncogenic activation of EGFR signaling through regulating ADAM17 activity in NSCLC.…”
Section: Ereg In Oncogene-driven Nsclcmentioning
confidence: 99%
“…Ovarian xenograft tumour model [170]. Triple negative breast cancer [171] A9(B8) Humanised mouse IgG2 antibody NSCLC with erlotinib/ gefitinib [172].…”
Section: D1(a12)mentioning
confidence: 99%